Non-standard work and fertility: a comparison of the US and Japan. Issue 2 (4th May 2018) - Piotrowski, Martin; Kalleberg, Arne; Bond, Erik; Wolford, Rick
ABSTRACT: Using General Social Survey data from Japan and the US ( N = 5101), we examine the effect of non-standard or non-regular work status on men's fertility. We employ a cross-national comparative approach to explore how this relationship differs both within and across the two countries. Consistent with features of the Japanese context which make it challenging for non-regular workers to realise the breadwinner role we find a negative effect of non-standard work status on men's fertility in Japan, but not the US. Specifically, Japanese men employed as non-regular workers have the lowest chances of having a child. Non-regular work status has no such effect on men's fertility in the US. We also find that the difference in the non-standard work effect between the two countries can be accounted for by differences in the effect of marriage, which illustrates the close connection between marriage and fertility in Japan.